Waterfront Design : A Case Study of the Coast of Misurata City (Jannat Area) (Journal of Academic Research, 2024)
The waterfront is one of the most challenging urban areas and provides enormous opportunities for urban development not only for the waterfront but also for the city as a whole. The communities surrounding the bodies of water are characterized by features that help them adapt to economic and social conditions, and in our present time they have moved away from the stereotypical idea of ​​using the coasts for trade, transportation, and industry. Rather, they have also become used as places for entertainment and amusement, attracting citizens and tourists. This research focus on a specific area which is the coastal strip of the city of Misurata overlooking the Mediterranean Sea, which is 23.5 meters long. The Jannat Beach area was chosen as a study sample for the seafront because it is located almost in the middle of the areas overlooking the coast and because it contains the highest peak of the petrified mountains found in the region. This study aims to clarify the importance of using the waterfront in developing cities and stimulating trade and tourism there, with a focus on entertainment and lifestyle, providing many amenities, using sustainable methods and exploiting the topography of the site to highlight its beauty, giving an overview of the development of the waterfront and discussing the principles of facade development. The successful marine project will serve as a guide for developing the waterfront of the city of Misurata.